2018
DOI: 10.3390/vetsci5020052
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition of Six Selected Neo-Tropical Mammals in Trinidad and Tobago with the Potential for Domestication

Abstract: This review highlights the available literature on the nutrition of six neo-tropical animals with the potential for domestication—the agouti (Dasyprocta leporina/D. aguti), lappe (Agouti paca), capybara (Hydrochoerus hydrochaeris), manicou/opossum (Didelphis marsupialis insularis), collared peccary (Peccary tajucu) and the red brokcet deer (Mazama americana). Over 100 references were used, spanning over 100 years. The earliest being 1915 and the most recent being 2018. The references used in this review were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 85 publications
(112 reference statements)
0
19
0
Order By: Relevance
“…Dookie et al [15] reported a feed particle size preference of 12.7 mm × 25.4 mm. Lall et al [16] reviewed the diets of these animals in captivity and in the wild. It was summarised that the agouti was frugivorous, herbivorous and opportunistic in its feeding behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Dookie et al [15] reported a feed particle size preference of 12.7 mm × 25.4 mm. Lall et al [16] reviewed the diets of these animals in captivity and in the wild. It was summarised that the agouti was frugivorous, herbivorous and opportunistic in its feeding behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…They have small home ranges and are essential as seed dispersers [ 2 , 3 ]. They are monogastric mammals that practice caecotrophy and coprophagy [ 4 ]. Wild agoutis have been reported to consume pulp from fruits that are plentiful and the seeds when fruits are scarce [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the agouti, D. leporina, has been studied in more detail, with focus on the anatomy of the male and female reproductive system, oestrus cycle in the female (28-31 days) as well as semen analysis using electroejaculation [5][6][7][8] Further anatomical investigations of the digestive system of the agoutis revealed that the majority of the gastrointestinal tract was small intestine in conjunction with a large cecum [9]. The agoutis mainly are frugivorous with the majority of the diet consisting of nuts and fruits, with potentially a preferential particle size [10][11][12][13]. Earlier it was found that these animals were rather omnivorous and would consume eggs and chicks [14].…”
Section: Introductionmentioning
confidence: 99%
“…The lappe was decribed as a frugivore, the manicou as an omnivore, the collared peccary as a pseudo-ruminant herbivore, and the red brocket deer was grouped with ruminants [12][13][14][15][16][17][18][19]. The manicou has a gestation period of three weeks [17,18].…”
Section: Introductionmentioning
confidence: 99%